Frontispiece: New Insight into the Hydrocarbon‐Pool Chemistry of the Methanol‐to‐Olefins Conversion over Zeolite H‐ZSM‐5 from GC‐MS, Solid‐State NMR Spectroscopy, and DFT Calculations. Issue 39 (22nd September 2014) - Wang , Chao; Chu , Yueying; Zheng, Anmin; Xu, Jun; Wang, Qiang; Gao, Pan; Qi, Guodong; Gong, Yanjun; Deng, Feng
<x xml:space="preserve">Abstract</x> Hydrocarbon‐pool chemistry plays a critical role in methanol‐to‐olefins reaction, but in‐depth understanding of the reaction pathway still remains a big challenge. Over archetype H‐ZSM‐5 zeolite, the observation and identification of carbocations is reported under working conditions. A paring route for producing propene in an aromatic‐based catalytic cycle is described by connecting the polymethylbenzenes and the carbocations. For more details, see the Full Paper by J. Xu, F. Deng et al. on page^^12432^^ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>